Perilaku pengelolaan sampah rumah tangga melalui edukasi berbasis behavior change communication (BCC): Studi di Kota Salatiga - Fetria Eka Yudiana; Joko Setyono (Nur Science Institute, 2026)
The issue of household waste in Indonesian cities shows a significant upward trend in line with the growing number of households. In the city of Salatiga, an average of around 80 tons of waste per day is processed at the Ngronggo landfill, with organic waste and plastic being the main contributors to household waste. Data also shows that the number of households is likely to increase by 8.85% in the 2017–2024 period, which will affect the overall volume of waste. This study evaluates changes in household waste management behavior through Behavior Change Communication (BCC)-based education on waste banks in Salatiga City. This study used a quasi-experimental design with a pre-test and post-test, involving 50 respondents across two neighborhood associations. The research instruments included questionnaires on knowledge, attitudes, and waste management practices, which were analyzed using a paired sample t-test. The results showed a significant increase in all indicators after the BCC intervention, indicating that this approach is effective in encouraging changes in household waste management behavior.